Address from Dean of The Faculty of Dentistry Universitas Gadjah Mada - Iwa Sutardjo Rus Sudarso (Fakultas Kedokteran Gigi, Universitas Gadjah Mada, 2010)
As mentioned in its Strategic Plans (2008-2012), Universitas Gadjah Mada (UGM) has its vision to be a World Class Research University which is excellent, independent, dignified, inspired by Pancasila, the five-point ideology, and dedicated to the needs and welfare of the nation and the world. The vision is done by UGM mission: To promote excellent teaching-learning opportunities and community service through research, with its special mission on research; To promote excellence in educational activities, research, and community service with the interest of the Indonesian society and to participate in Indonesian socioculturalbuilding.As a university unit, Faculty of Dentistry should play significant roles towards the vision. For this, research indeed is one of important factors towards the vision. To get better of research’s result application and social service, it is hoped that researcher possesses entrepreneurial ability while still maintaning his/her research quality. It can be said that, generally, research development in the Faculty of Dentistry is growing satisfactorily. But, still, it is not yet followed by strong publication. One of bestknown research publications is academic journal, nationally or internationally. This kind of publication is an effective form of communication among researchers and also a very considerable part in scientific and technological development.Considering the above driving forces and the uniqueness of the country in relation to researches in dental sciences, Faculty of Dentistry proudly publish “The Indonesian Journal of Dental Research” which is in turn to be a window for the international forum to learn on the progresses and achievements in dental research in Indonesia. In the future, it is also hoped that “The Indonesian Journal of Dental Research” be an information portal in terms of dental science and technology in Indonesia, and in the Asian region in general.Hopefully, this journal will be able to provide scientific media for sharing progresses and achievements in research on oral and dental sciences in Indonesia to the international forum. Moreover, this journal is expected to be an embrio for scientific portal in dental and oral sciences in Indonesia and Asia region.Iwa Sutardjo RSProfessor in Pediatrics DentistryDean of The Faculty of DentistryUniversitas Gadjah Mada